Extraction, purification and characterisation of bromelain from pineapple crowns and its application / Nadzirah Kamarul Zaman - Kamarul Zaman, Nadzirah (Institute of Graduate Studies, UiTM, 2016)
Pineapple crowns are an agricultural waste available in large quantity particularly from canned pineapple industry. Alternatives to its efficient utilisation are necessary as the crowns contain high enzyme activity which can be potentially used as a meat tenderiser. Thus, the aims of this study are to extract and purify bromelain from the pineapple crowns. The purified bromelain was freeze dried to produce bromelain powder which was later applied to tenderise the toughest Brahman part, round. The action of bromelain in tenderising beef was affected by different pHs of beef, immersion temperatures and times, and bromelain solution concentrations. Thus, response surface methodology (RSM) was used to determine the feasible optimum condition for the beef tenderisation by bromelain. The effect of bromelain treatment on the physico-chemical properties of beef and its nutritional quality was determined. The nutritional quality of beef was determined from the proximate extent between the bromelain-treated beef and the reference pattern protein and compared with the untreated beef. SDS-PAGE revealed that bromelain from pineapple crowns is a monomeric with a molecular weight of 30 kDa. The bromelain powder was less pure compared to that of standard bromelain powder…